New polarization and power calculations with error elimination in ternary QCA. (December 2021) - Akbari-Hasanjani, Reza; Sabbaghi-Nadooshan, Reza; Tanhayi, Mohammad Reza
Abstract: Quantum cellular automata (QCA) is a promising technology for replacing MOS transistors in digital and computing systems. Recently, many efforts have been made to design complex structures using Binary QCA (bQCA) cells, researchers' attention has been drawn to multilevel structures using QCA technology, and Ternary QCA (TQCA) cells have been introduced. Many researchers have studied the structure of the TQCA cell, and several models have been proposed to design the AND and OR gates. This paper investigated the polarization in TQCA using two electron particles and eight potential wells. The distance between wells and the cell wall was also changed, and the error in the AND and OR gates was eliminated by using TQCA in one phase clock. In the following calculations, the power dissipation of TQCA cells in different polarizations and the upgrade of TQCA Sim software to implement basic gates using the performed calculations have been investigated. Graphical abstarct: Image, graphical abstract